Field Dependence / Field Independence as a Factor of Individual Travel Style - Milutina, Kateryna; Obukhova, Margarita (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Means of restoring a normative mental state, increasing stress resistance is the most urgent problem today. Traveling as a way of leisure and recreation began not so long ago - from the second half of the 20th century. The desire for changes and life movement is an unconscious natural desire for the development and manifestation of individual research strategies and cognitive processes, that is, cognitive style. The purpose of our article is to highlight the results of a pilot study of the connection between field dependence and field dependence with an individual style of recreational activity (travel). Methods. The following methods were used: the Gottschaldt test of included figures, a questionnaire and an in-depth interview: The sample consisted of 20 people (N=20), of which 11 were women and 9 were men, aged from 20 to 25 years. All participants took part in the survey voluntarily, with informed consent. Results. It was found that among field-dependent respondents, 7 people chose "within the country", "abroad" and "in nature", 3 people -"around their city" and "to "exotic" countries" as a travel option. As a method of travel, 8 people chose "plane", 5 - "on foot" and "bus", 4 - "train" and "car". No one chose "bicycle or boat". In terms of travel environment preferences, 5 people would prefer to travel alone, 9 in pairs. As a travel option, among field-independent people, 5 people chose "around their city" and "abroad", 4 - "to "exotic" countries", 3 - "in nature" and "around their city". As a method of travel, 6 people of the rite of passage "on foot", 4 - "car" and "plane", 3 - "train", "bus" and "bicycle". The choice of travel environment was as follows: 5 people chose "alone" and "in pairs", 3 - "with a tourist group". It is interesting that field-independent respondents did not choose the options "in their city" and much less often - "in nature". Conclusion. It was established that field-dependent individuals tend to choose to travel alone or in pairs. Instead, field-independent respondents more often prefer to travel within their country or abroad, sometimes by train, bus or bicycle, but are ready to spend this time either independently, as a couple or with a tourist group.